National Accounts Statistics : main aggregates and detailed tables, 1982 - United Nations (New York : United Nations, 1985)
This book of yearbook shows detailed national accounts estimates for 159 countries and areas.
(Replaces 1982 yearbook of National Accounts Statistics, volume I, parts 1 and 2, individual country data)
hza 01/02/2019
Loans
Keywords: Year books